PENGARUH SUSTAINABILITY REPORT DENGAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Luh Pande Eka Setiawati; I Kadek Bagiana (UNHI Press, 2024)
The Effect of Sustainability Report with Good Corporate Governance on Company Performance. Disclosure of sustainability reports provides added value for companies, however because there are still inconsistencies in research results, to reduce research bias the GCG mechanism is used as a moderating variable. Sustainability reports must be equipped with three main aspects, namely economic, social and environmental. GCG is a guideline that must be met by companies in operating so that the company operates in accordance with stakeholder needs. This research uses 30 companies observed in the manufacturing sector for the 2020-2022 period. The data analysis technique used is MRA. The research results show that of the four GCG mechanisms, only two are able to moderate the direct influence relationship, namely the board of commissioners and foreign ownership, while the board of directors and managerial ownership are unable to moderate this direct relationship.